RIFM fragrance ingredient safety assessment, isobutyl alcohol, CAS Registry Number 78-83-1. (December 2019) - Api, A.M.; Belmonte, F.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; et al.
Abstract: Summary: The existing information supports the use of this material as described in this safety assessment. Isobutyl alcohol was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data show that isobutyl alcohol is not genotoxic. Data on isobutyl alcohol provide a calculated MOE >100 for the repeated dose toxicity and reproductive toxicity endpoints. Data from read-across material isoamyl alcohol (CAS # 123-51-3) show that there are no safety concerns for isobutyl alcohol for skin sensitization under the current declared levels of use. The phototoxicity/photoallergenicity endpoints were evaluated based on UV spectra; isobutyl alcohol is not expected to be phototoxic/photoallergenic. The local respiratory toxicity endpoint was evaluated using the TTC for a Cramer Class I material and the exposure to isobutyl alcohol is below the TTC (1.4 mg/day). The environmental endpoints were evaluated; isobutyl alcohol was found not to be PBT as per the IFRA Environmental Standards, and its risk quotients, based on its current volume of use in Europe and North America (i.e., PEC/PNEC), are <1. Highlights: Isobutyl alcohol; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.